Antitumor Effect of Fluoxetine on Chronic Stress-Promoted Lung Cancer Growth via Suppressing Kynurenine Pathway and Enhancing Cellular Immunity - Yang, Zhen; Li, Zhuman; Guo, Zhijun; Ren, Yu; Zhou, Ting; Xiao, Zhijun; Duan, Jingjing; Han, Chuangchuang; Cheng, Yuanchi; Xu, Feng (Frontiers in Pharmacology, 2021)
Background：Chronic stress promotes cancer growth. Antidepressant fluoxetine (FLX) is usually prescribed for cancer patients comorbidity with depression. FLX displays inhibition on cancer cell proliferation, however, the in vivo activity has not been investigated. Methods: We explored the antitumor effect of FLX in subcutaneous transplanted lung cancer cells tumor-bearing mice model. Fifty-six C57BL/6 mice were randomly divided into group A (blank control), group B (tumor-bearing control), group C (tumor-bearing + FLX), group D (CUMS control), group E (CUMS + FLX), group F (tumor-bearing + CUMS), group G (tumor-bearing + CUMS + FLX). 5-HT, tryptophane (Trp), kynurenine, IFN-γ, TNF-α, IL-1α, IL-1β, IL-2, IL-4, IL-6, IL-10, IL-17A levels were measured by ELISA. T helper (Th), cytotoxic T (Tc) and regulatory T cells (Tregs) subtype were measured by flow cytometry. The antitumor effects of FLX were evaluated by tumor weight. The expression of kynurenine pathway related genes TDO, IDO1, IDO2, and apoptosis-related genes caspase1, 3, 4, 5, 7, 12 in tumor tissues were measured by western blotting and qRT-PCR. A549 cells were exposed with FLX (15 μmol/L) and its effect on cell proliferation, migration, clonal formation were detected. Kynurenine pathway and apoptosis related genes expression were also measured. Results: In vivo, chronic stress promoted tumor growth in C57BL/6 mice. FLX administration significantly not only reversed CUMS-induced reduction of 5-HT and Trp, increment of kynurenine, but increased CD4+ Th and CD8+ Tc cells, and reduced CD25+ FOXP3+ Tregs. FLX promoted Th to differentiate into Th1 cells and increased IL-2 and IFN-γ, meanwhile inhibited Th differentiate into Th2, Th17 cells and decreased the concentrations of IL-4, IL-6, IL-10, IL-17A. Chronic stress obviously up-regulated IDO1, IDO2 expression，down-regulated caspase 4, 7, and 12 expression, meanwhile FLX administration reversed this regulation. However, there was no significant change in TDO, caspase 1, 3, 5. Similarly, in vitro, FLX administration significantly inhibited the proliferation, migration, clonal formation of A549 cells and induced cells apoptosis. FLX administration down-regulated the expression of IDO1, IDO2 and up-regulated caspase 4, 5, 7. Conclusion: Fluoxetine administration could inhibit tumor growth. The inhibition might be via suppressing kynurenine pathway and enhancing cellular immunity.